Una función de producción agregada para la economía colombiana: características e interacción entre el trabajo calificado, el trabajo no calificado y el capital, 1994–2005. (2008)
This paper estimates the skilled labor, unskilled labor and capital elasticities when it is assumed a translogarithmic production function for the Colombian economic. It is found that the skilled labor remuneration has risen its participation while the other production factors remuneration have gotten down. In general, the production factors are normal goods, but the skilled labor is the factor that has more reaction to changes to the aggregate production. On the other hand, the unskilled labor is the factor that has the highest price elasticity to the demand in absolute value. Finally, it is found that there is a complementary relation between the skilled labor and the other factors, but there is a substitution relation between the unskilled labor and the capital. These microeconomic facts join to the lower capital cost and the higher unskilled labor price explain the small fall in the unemployment rate while the macroeconomic environment is good.